2014
DOI: 10.7314/apjcp.2014.15.18.7563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viral Hepatitis-Associated Hepatocellular Carcinoma Due to HBV and HCV - Cohort from Liver Clinics in Pakistan

Abstract: Conclusions: Statistically significant variations were observed from baseline to clinical-pathological characteristics in HCV vs HBV associated HCC. Our study suggests prompt and early screening for high risk patients so that the rate of progression of these chronic viral diseases to cirrhosis and cancer can be decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The frequency of HCV is highest in few countries and areas, such as in Europe 25 million cases are HCV positive [17]. In Pakistan, HCV is 5% prevalent [18], whereas 5-9% prevalence is detected in Khyber Pakhtunkhwa province of Pakistan [19] causing liver cancer [20]. HCV-4 is prevalent among Middle East and Africa causing more than 80% of HCV infections and has recently spread to several European countries.…”
Section: Frequency Of Hcv Genotypes and Infectionsmentioning
confidence: 99%
“…The frequency of HCV is highest in few countries and areas, such as in Europe 25 million cases are HCV positive [17]. In Pakistan, HCV is 5% prevalent [18], whereas 5-9% prevalence is detected in Khyber Pakhtunkhwa province of Pakistan [19] causing liver cancer [20]. HCV-4 is prevalent among Middle East and Africa causing more than 80% of HCV infections and has recently spread to several European countries.…”
Section: Frequency Of Hcv Genotypes and Infectionsmentioning
confidence: 99%
“…Hep-C is the most common etiology in up to 58% patients and hep-B in 25.3% cases [ 13 ]. Results from larger studies ( N ≥ 100) on HCC are conflicting where anti-HCV antibody positivity ranges between 24 and 72.5% while HbsAg positivity varies between 13.1 and 51.2% [ 9 , 26 – 31 ]. This can be attributed to patchy nature of available information, high prevalence of hep-C in certain regions of the country, and lack of national cancer surveillance.…”
Section: Risk Factors and Epidemiologymentioning
confidence: 99%
“…Therefore, our subgroup analysis should pay attention to the tendency that high SAC3D1 expression is associated with bad prognosis, not statistical significance. Some studies reported that patients with hepatitis B have better prognosis compared to patients with hepatitis C virus 36 , 37 . The TCGA analysis in Table 3 shows interesting results.…”
Section: Discussionmentioning
confidence: 99%